Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T16:03:35+01:00
A) 2x + 3y = 14
3x - 2y = 8 | *2

2x + 3y = 14
6x - 4y = 16

2x= 14 - 3y
3*(14 - 3y) - 4y = 16

2x = 14 - 3y
42 - 9y - 4y = 16

2x = 14 - 3y
- 9y - 4y = 16 - 42

2x = 14 - 3y
- 13y = - 26

2x = 14 - 3y
y = 2

2x = 14 - 3 * 2
y = 2

2x = 14 - 6
y = 2

2x = 8
y = 2

x = 4
y = 2
1 1 1
2010-01-25T16:42:51+01:00
{2x+3y=14|:2
3x-2y=8
{x+1,5y=7
3x-2y=8
{x=7-1,5y
3(7-1,5y)-2y=8
{x=7-1,5y
21-4,5y-2y=8
{x=7-1,5y
-6,5y=8-21
{x=7-1,5y
-6,5y=-13|:(-6,5)
{x=7-1,5y
y=2
{x=7-1,5*2
y=2
{x=7-3
y=2
{x=4
y=2